A Case Study of Secondary Science Teachers in Utilizing Online Tools in Blended Modality - Ramos, Dave C.; Taghap, Raffy S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Educational institutions are keeping up with changes in time. When COVID-19 hindered the traditional face-to-face classroom set-up, several forms of education, including blended learning, had to be implemented. Blended learning was possible due to the current advancement in science and technology. Applications and online tools are available for teachers and learners to ascertain the continuity of education. Hence, this study explores the online tools and applications utilized by science teachers, challenges encountered, and coping mechanisms teachers utilize to counter challenges. Moreover, this study employs a case study approach to ascertain that the data gathered are contextualized and specific. The results revealed that teachers utilized online tools like Class Point, Quizziz, E-class (Moodle), Kahoot, and Peer Deck. Challenges encountered by teachers include Lack of Digital Competence, Incompatibility of the application to the gadget used, Unstable internet connection, Lack of access to online tools premium features, and Lack of student engagement and direct supervision. Moreover, the teachers' coping mechanisms include Using differentiated and collaborative activities and emphasizing authentic submission of outputs. To effectively develop and implement these tools, it is necessary to comprehend and attend to the needs of secondary science teachers who have shared their experiences using online tools in a blended modality.